(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, raising the awareness of legal knowledge and culture of young people means that they actively react to changes in social life, express their personal opinions, contribute to the development of society, raise the legal culture of the growing young generation, grow. At the same time, it is directly related to the reform of the state and society, the critical analysis of the current legal documents, the introduction of appropriate changes to the current laws based on the requirements of the time, and the abolition of outdated norms that are an obstacle to development. analyzed in examples.